2007
DOI: 10.1097/med.0b013e3280123119
|View full text |Cite
|
Sign up to set email alerts
|

The role of peptide YY in integrative gut physiology and potential role in obesity

Abstract: These findings lend some support for the association between PYY and obesity that could lead to possible new therapeutic options in obesity. PYY exerts anorexigenic effects; it is possible that surgical weight-loss procedures work synergistically with PYY to promote weight loss. Further investigation is needed to clarify whether PYY actually causes reduced calorie intake or whether the rate of food delivery to the ileo-colonic segment influences PYY levels, thus affecting satiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In addition to these direct effects mediated by TGR5 receptors on target cells, bile salts are likely to have indirect effects on gut motility. Both GLP-1 and PYY are shown to regulate gastrointestinal functions, especially proximal gut motility and secretion (Grudell and Camilleri, 2007; Holst, 2007; Kidd et al, 2008; Hellstrom, 2010; Holzer et al, 2012). The biological functions of PYY include attenuation of food intake, and gastric emptying and motility, and gastric secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these direct effects mediated by TGR5 receptors on target cells, bile salts are likely to have indirect effects on gut motility. Both GLP-1 and PYY are shown to regulate gastrointestinal functions, especially proximal gut motility and secretion (Grudell and Camilleri, 2007; Holst, 2007; Kidd et al, 2008; Hellstrom, 2010; Holzer et al, 2012). The biological functions of PYY include attenuation of food intake, and gastric emptying and motility, and gastric secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The biological functions of PYY include attenuation of food intake, and gastric emptying and motility, and gastric secretion. PYY modulates gastrointestinal functions and motility partly via its action on myenteric neurons and smooth muscle but also through central effects mediated by the vagus (Grudell and Camilleri, 2007; Holzer et al, 2012). This latter mechanism is especially noteworthy in the postprandial state where PYY has been shown to participate in the inhibition of gastric motility and secretion when intraluminal stimuli reach the distal gut, a phenomenon known as the ileal brake (Grudell and Camilleri, 2007; Holzer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that circulating PYY exerts a stimulatory action on appetite through Y1 (NPY1R) receptors and an inhibitory action through Y2 (NPY2R) receptors (39). Although recent studies focused largely on the anorexigenic effect of PYY administered peripherally (40), centrally infused PYY was originally discovered as a potent orexigenic agent, producing hyperphagia in rodents when injected into cerebral ventricles, paraventricular nucleus, or hippocampus (41,42). Chronic central administration of PYY augmented feeding and drinking, without development of tolerance, suggesting PYY may play a role in the pathogenesis of bulimic syndromes (43).…”
Section: Endocrinology Of Human Body Mass: Hypothesismentioning
confidence: 99%
“…PYY is also involved in regulating insulin secretion and glucose homeostasis. There are reports that fasting and postprandial PYY levels are decreased in obese subjects (Grudell and Camilleri, 2007) and that overweight subjects have a relative deficiency of postprandial PYY release that is associated with reduced satiety (Coll et al, 2007).…”
Section: Gut Hormones Related To Satietymentioning
confidence: 99%